Industrialisation in the periphery: Southern Rhodesian and South African trade relations between the wars - Phimister, Ian (My University, 1986)
Over the last two decades the process of industrialisation in Africa has generated considerable scholarly interest and debate. While much of the interest flows from industry's acknowledged potential as ‘the main lever of African development’, most of the debate concerns the reasons for its generally poor performance. Broadly speaking, opinion is divided between those writers who emphasize the 'major external constraints limiting industrialization', and others who analyse industrialisation in terms of ‘'internal forces [which] help or hinder it’. To date, these issues have been most exhaustively explored in the ‘Kenya Debate’ By comparison, analysis of Zimbabwe's much larger industrial sector has lagged far behind. Although developments since 1965, particularly the role and significance of foreign capital, have been studied, neither the origins nor the nature of Zimbabwean industrialisation have received much attention. In seeking to open these topics for discussion, this paper argues that the growth of local secondary industry was crucially conditioned by the interwar pattern of Southern Rhodesia's trade relations with South Africa.
African Studies Seminar series. Paper presented 28 July 1986
Keywords: Industries. Zimbabwe; Zimbabwe. Commerce. South Africa; South Africa. Commerce. Zimbabwe